Closing the book: including improvisation in the private piano lesson - Lemoine, Nicole Jeanette (Kansas State University, 2015)
This Lecture Recital, given in lieu of a Master’s Report, was on the use of improvisation as a teaching aid in the private piano lesson. The lecture and supplemental handout included an historical overview of the role of improvisation, research on its educational benefits in regards to student learning, and a review and demonstration of current piano method books designed to teach the concept of improvisation. A bibliography of sources used in the presentation, as well as reviewed articles, books, and websites were included in the handout. The piano method books reviewed are Scott McBride Smith’s American Popular Piano, and Pattern Play, by Forrest Kinney. This graduate lecture recital was given in partial fulfillment of the requirements for the Master of Music degree in piano pedagogy on February 25, 2015 in Kirmser Hall at Kansas State University. It featured demonstrations with the aid of Leah Harmon on piano.
Keywords: piano improvisation; music teaching lessons; Music Education (0522)